The Role of Innovation Strategy Mediation in Rivalry Relationships with the Organizational Performance : Peran Mediasi Strategi Inovasi dalam Hubungan Rivalitas terhadap Kinerja Organisasi Perguruan Tinggi - Widodo, Heri; Tjahjadi, Bambang; Basuki, Basuki (Universitas Muhammadiyah Sidoarjo, 2022)
This research is expected to prove that the innovation strategy mediates the effect of the level of rivalry on organizational performance at the Muhammadiyah 'Aisyiyah College (PTMA). The population in this study were all active Muhammadiyah 'Aisyiyah Universities (PTMA) in Indonesia, as many as 164 PTMAs consisting of universities, high schools, polytechnics, institutes, and academies. Samples were taken as many as 70 PTMA with the technique of determining the sample used was random sampling. The data analysis techniques used were Common Method Biases (CMB) and Partial Least Square-Structural Equation Modeling (PLS-SEM). The results of the study prove that the Innovation Strategy is able to mediate the effect of rivalry on organizational performance. PTMA's ability to adapt as well as the ability to choose strategies will be a determining factor in maintaining and improving operational sustainability, competitiveness and improving PTMA organizational performance. The innovation strategy used in this research is an IT-based academic program strategy, the development of open learning through SiberMu, or a merger policy between PTMA. The results of this study provide empirical evidence on the Industrial Organizational (I/O) theory, which is related to the level of competition. Rivalry mediated by innovation strategies can improve organizational performance. The results of this study indicate that the increase in organizational performance will be influenced by the external conditions of the organization, namely rivalry. The results of this research are practically expected to contribute to policy and strategy development for PTMA leaders in facing the Industrial Revolution 4.0 era.